Patient compliance as a risk factor for the outcome of implant treatment. Issue 1 (12th August 2019) - Cortellini, Simone; Favril, Charlotte; De Nutte, Mathieu; Teughels, Wim; Quirynen, Marc
Abstract: Peri‐implantitis can be explained using a multicausality model. Many factors are involved in the etiology of peri‐implantitis, but patient compliance also plays a key role. Oral hygiene, attending recall visits, smoking behavior, and therapy comprehension are relevant factors that contribute to peri‐implant health. The clinician should create the most optimal conditions for patients to facilitate adequate oral self‐care and to help patients improve their oral hygiene skills. Implementation of a supportive periodontal therapy program is mandatory to control inflammation and plaque accumulation, as well as to keep the incidence of peri‐implant diseases low. Patient compliance, including plaque control and dental follow‐up, must be optimal. Consequently, precautions must be taken with patients treated with dental implants.